Development and optimization of red spectrum splitting concentrated agrivoltaic system for energy generation and sustainable agriculture - Ngoc-Hai Vu; Tran Quoc Tien; Ngoc-Minh Kieu; Thanh-Phuong Nguyen; Quang Cong Tong; Seoyong Shin (PLoS ONE, 2025)
Agricultural land is increasingly under pressure from expanding solar energy infrastructure, leading to a growing conflict between food and energy production. Conventional photovoltaic (PV) systems often reduce crop yields due to shading and suboptimal light conditions for photosynthesis. This study introduces a Red Spectrum Splitting Concentrated Agrivoltaic (RSSCA) system designed to overcome these limitations by selectively directing specific wavelengths of sunlight to serve both agricultural and energy needs. The system uses a Fresnel lens and dichroic mirror to concentrate solar radiation and split the spectrum: red light (around 630 nm), essential for rice growth, is transmitted to the crops, while the remaining wavelengths are directed to high-efficiency multi-junction solar cells. We employed optical simulations and analytical modeling to assess system performance. Results show a photoelectric conversion efficiency of 31.2% and adequate Daily Light Integral (DLI) levels for rice cultivation in high-sunlight regions such as Hanoi and Ho Chi Minh City. For instance, DLI values in Hanoi range from 14.3 to 32.2 mol/m2/day and in Ho Chi Minh City from 24.3 to 37.8 mol/m2/day, compared to 6.6–16.1 and 14.4–18.2 mol/m2/day under conventional PV systems, respectively. Electricity production with RSSCA peaks at 2790 W/m2/day in Ho Chi Minh City and 2577 W/m2/day in Hanoi, outperforming traditional PV setups by 3–5 times. Compared to conventional PV systems, the RSSCA offers improved light uniformity, better land-use efficiency, and significantly higher electricity generation. However, in regions with limited direct sunlight, such as Seoul in winter, system performance decreases. These findings suggest the RSSCA system is well-suited for tropical and subtropical areas where direct sunlight is abundant. It presents a viable solution for enhancing both food production and renewable energy generation on shared land.